ANALISIS PENGARUH ZAKAT TERHADAP INDEKS PEMBANGUNAN MANUSIA (IPM) MUSTAHIK (STUDI KASUS: BAITUL MAL KOTA BANDA ACEH) - Sarah Syukri; Eddy Gunawan (FEB Universitas Syiah Kuala, 2020)
This study aims to analyze influence zakat programs of Baitul Mal Banda Aceh on Human Development Index (HDI) of Mustahik. The population of this study is all Mustahik who receive productive-based zakat amounted 504 people, and the samples of this study are 100 people selected by purposive sampling technique. The simple regression analysis were respectively used. The result of this study indicate that zakat was insignificant influencing towards life expectancy and education index, but zakat had significant influence on purchasing power index. From the results of this study suggest that Baitul Mal Banda Aceh allocate zakat funds more effectively and efficiently, by expanding the allocation of zakat to the health sector, and the education sector. So zakat will have an influence on improving of human development.